Intermittent Theta Burst Stimulation Ameliorates Cognitive Deficit and Attenuates Neuroinflammation via PI3K/Akt/mTOR Signaling Pathway in Alzheimer’s-Like Disease Model - Stekic, Andjela; Zeljkovic, Milica; Zaric Kontic, Marina; Mihajlovic, Katarina; Adzic, Marija; Stevanovic, Ivana; Ninkovic, Milica; Grkovic, Ivana; Ilic, Tihomir V.; Nedeljkovic, Nadezda; Dragic, Milorad (Frontiers in Aging Neuroscience, 2022)
Neurodegeneration implies progressive neuronal loss and neuroinflammation further contributing to pathology progression. It is a feature of many neurological disorders, most common being Alzheimer’s disease (AD). Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive stimulation which modulates excitability of stimulated brain areas through magnetic pulses. Numerous studies indicated beneficial effect of rTMS in several neurological diseases, including AD, however, exact mechanism are yet to be elucidated. We aimed to evaluate the effect of intermittent theta burst stimulation (iTBS), an rTMS paradigm, on behavioral, neurochemical and molecular level in trimethyltin (TMT)-induced Alzheimer’s-like disease model. TMT acts as a neurotoxic agent targeting hippocampus causing cognitive impairment and neuroinflammation, replicating behavioral and molecular aspects of AD. Male Wistar rats were divided into four experimental groups–controls, rats subjected to a single dose of TMT (8 mg/kg), TMT rats subjected to iTBS two times per day for 15 days and TMT sham group. After 3 weeks, we examined exploratory behavior and memory, histopathological and changes on molecular level. TMT-treated rats exhibited severe and cognitive deficit. iTBS-treated animals showed improved cognition. iTBS reduced TMT-induced inflammation and increased anti-inflammatory molecules. We examined PI3K/Akt/mTOR signaling pathway which is involved in regulation of apoptosis, cell growth and learning and memory. We found significant downregulation of phosphorylated forms of Akt and mTOR in TMT-intoxicated animals, which were reverted following iTBS stimulation. Application of iTBS produces beneficial effects on cognition in of rats with TMT-induced hippocampal neurodegeneration and that effect could be mediated via PI3K/Akt/mTOR signaling pathway, which could candidate this protocol as a potential therapeutic approach in neurodegenerative diseases such as AD.